2013
DOI: 10.1242/dev.098343
|View full text |Cite
|
Sign up to set email alerts
|

Ribosome profiling reveals resemblance between long non-coding RNAs and 5′ leaders of coding RNAs

Abstract: SUMMARYLarge-scale genomics and computational approaches have identified thousands of putative long non-coding RNAs (lncRNAs). It has been controversial, however, as to what fraction of these RNAs is truly non-coding. Here, we combine ribosome profiling with a machine-learning approach to validate lncRNAs during zebrafish development in a high throughput manner. We find that dozens of proposed lncRNAs are protein-coding contaminants and that many lncRNAs have ribosome profiles that resemble the 5Ј leaders of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
310
0
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 253 publications
(322 citation statements)
references
References 60 publications
6
310
0
2
Order By: Relevance
“…Considering that its full length contained an open reading frame for a peptide of 62 amino acids, lncPrep+96kb might possibly be translated to a peptide. Indeed, recent ribosome profiling analyses indicated that many lncRNAs were bound by ribosomes (42,43). However, other studies argued that a majority of lncRNAs did not encode proteins (44,45), suggesting the function of lncPrep+96kb as an RNA molecule.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that its full length contained an open reading frame for a peptide of 62 amino acids, lncPrep+96kb might possibly be translated to a peptide. Indeed, recent ribosome profiling analyses indicated that many lncRNAs were bound by ribosomes (42,43). However, other studies argued that a majority of lncRNAs did not encode proteins (44,45), suggesting the function of lncPrep+96kb as an RNA molecule.…”
Section: Discussionmentioning
confidence: 99%
“…To further assess the conservation of NED we used ribosome profiling data from different species (human, HEK293 (Liu et al, 2013), mouse (Shalgi et al, 2013), zebrafish (Chew et al, 2013) and C. elegans (Nedialkova and Leidel, 2015)). We classified proteins in these datasets according to the degradation profiles of their human orthologs (in RPE-1 cells).…”
Section: Ned Is Evolutionarily Conservedmentioning
confidence: 99%
“…The datasets for Human (SRA061778; HEK293 cells no treatment; (Liu et al, 2013)), Zebrafish (GSE46512; 28hours post-fertilization; (Chew et al, 2013) 5) and Shalgi et al 2013(Shalgi et al, 2013 (Fig. 6).…”
Section: Ribosomal Profiling Data Analysismentioning
confidence: 99%
“…Eukaryotic cells are lysed on ice by repeated micropipetting or homogenization (Guo et al, 2010;Becker et al, 2013;Chew et al, 2013). Pulverized bacteria or monocellular eukaryotes are homogenized in a mill with liquid nitrogen (Oh et al, 2011;Guydosh and Green, 2014;Woolstenhulme et al, 2015).…”
Section: Cell Lysismentioning
confidence: 99%
“…In the majority of ribosome profiling experiments (Ingolia et al, 2009(Ingolia et al, , 2011Guo et al, 2010;Gerashchenko et al, 2012;Li et al, 2012;Chew et al, 2013;Guttman et al, 2013;Aspden et al, 2014;Baudin-Baillieu et al, 2014;Bazzini et al, 2014;Subramaniam et al, 2014), Bowtie (Langmead et al, 2009) is used as a BWT-based mapping program. Bowtie offers two ways of mapping a read to a reference sequence: seed-(parameter n) and mismatchbased approach (parameter v, Table 1).…”
Section: Read Mappingmentioning
confidence: 99%